2014
DOI: 10.1159/000366361
|View full text |Cite
|
Sign up to set email alerts
|

IGF2R Expression is Associated with the Chemotherapy Response and Prognosis of Patients with Advanced NSCLC

Abstract: Background: Insulin-like growth factor (IGF) pathway has been suggested as a new molecular target for the treatment of cancer including Non-small cell lung cancer (NSCLC). We postulated that IGF-2 receptor (IGF2R) may be associated with treatment response and prognosis of NSCLC patients receiving chemotherapy. Methods: A total of 464 patients with inoperable advanced stage of NSCLC were enrolled. All patients received platinum-based chemotherapy. Meanwhile, the IGF2R expression in tumor samples was detected by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
1
24
1
1
Order By: Relevance
“…Also, report showed that activation of AMPK could stimulate IGFBP1 secretion, thereby overcoming the inhibitory effect of insulin in rat hepatoma cells [46]. While our results implicated a positive feedback regulatory loop of AMPKα signaling, the possible involvement of other kinase signaling pathways, and up- or downstream mediators underlying this regulation, such as phosphorylation and regulation of IGF-1 receptor [47, 48], regulation of IGFs [49], forkhead box class O (FOXO) [50], and hypoxia-inducible factor (HIF) [51], among others, required to be elucidated in the future studies. In addition to inhibiting IGF effects [52], IGFBP1 also showed to suppress cancer cell proliferation, invasiveness and motility via stimulating or inhibiting several critical downstream genes and/or proteins [51, 53], which highlighted a tumor suppressor role of IGFBP1.…”
Section: Discussionmentioning
confidence: 58%
“…Also, report showed that activation of AMPK could stimulate IGFBP1 secretion, thereby overcoming the inhibitory effect of insulin in rat hepatoma cells [46]. While our results implicated a positive feedback regulatory loop of AMPKα signaling, the possible involvement of other kinase signaling pathways, and up- or downstream mediators underlying this regulation, such as phosphorylation and regulation of IGF-1 receptor [47, 48], regulation of IGFs [49], forkhead box class O (FOXO) [50], and hypoxia-inducible factor (HIF) [51], among others, required to be elucidated in the future studies. In addition to inhibiting IGF effects [52], IGFBP1 also showed to suppress cancer cell proliferation, invasiveness and motility via stimulating or inhibiting several critical downstream genes and/or proteins [51, 53], which highlighted a tumor suppressor role of IGFBP1.…”
Section: Discussionmentioning
confidence: 58%
“…Chemoresistance, which leads to the failure of chemotherapy, is very common in the therapeutic process [8, 45, 46]. Thus, the development of effective chemotherapies is critical.…”
Section: Discussionmentioning
confidence: 99%
“…The circulating concentration of IGF1 is found to be associated with an increased risk of many cancers [19,20,21,22]. Besides, IGF2R expression is associated with the chemotherapy response and prognosis of patients with advanced non-small cell lung cancer [23] . Genetic factors could influence circulating IGF1 concentration [24].…”
Section: Introductionmentioning
confidence: 99%